The human digestive system (Chatsworth : AIMS Multimedia, 1997)
CD-ROM program contains a complete liner video, interactive quiz with video reinforcement, bulletin board, glossary, test with record keeping and teacher management system
Back-to-Basics
Keywords: Digestive system